Evaluation Of Risk Awareness Culture In A Strategic Holding Insurance Company - Adena Ramadhany; Aria Farah Mita (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This research aimed to evaluate the risk awareness culture in a Strategic Holding Insurance Company (PT XYZ) based on The Institute of Management (IRM) Risk Culture Framework by assessing individual and organizational perspectives. This study emphasized that a robust risk awareness culture is a foundation of risk management maturity. This research was a qualitative descriptive study with primary data obtained directly from the research object through surveys and interviews. Based on individual level analysis, the result shows personal predisposition average to low levels of risk tolerance. They tend to be uncomfortable taking risks without adequate analysis and calculation and had a prepared character. Based on organizational level analysis, PT XYZ organizational culture falls into the communal category which has high level of solidarity and social dimensions. People in this category are characterized by good teamwork across functions and have the same goal focus. Evaluation of the eight aspects based on IRM Risk Culture Aspects Model, there are four aspects that constitute leading practice (risk leadership, accountability, risk resources, and risk skill) and three aspects of good practice (reward, dealing with bad news and informed risk decisions) as well as one aspect of lag or gap practice (transparency).